Réponses

  • Utilisateur Brainly
2014-04-07T20:44:07+02:00
A= 9 (x-3)²-(x-2)²
=(3x-9-x+2)(3x-9+x-2)
=(2x-7)(4x-11)

B= 9x²-6x+1-(2x+3)²
=(3x-1)²-(2x+3)²
=(3x-1+2x+3)(3x-1-2x-3)
=(5x+2)(x-4)

C= (3x-1)(x+4)-18x²+12x-2

=(3x-1)(x+4)-2(3x-1)²
=(3x-1)(x+4-6x+2)
=(3x-1)(-5x+6)
Meilleure réponse !
2014-04-07T20:48:26+02:00
A = 9 (x-3)²-(x-2)²
   = 9 (x²-6x+9)-(x²-4x+4)
   = 9 x x² - 9 x 6x + 9 x 9 - x²+4x-4
   = 9x² - 54x + 81 - x² +4x -4
   = 9x² - x² -54x + 4x +81 - 4
   = 8x² - 50 x + 77

B = 9x² - 6x + 1 - (2x+3)²
   = 9x² - 6x + 1 -(2x x 2x + 2x x 3 x 2 + 3 x 3)
   = 9x² - 6x + 1 - (4x² + 12x + 9)
   = 9x² - 6x + 1 - 4x² -12x - 9
   = 9x² - 4x² -6x - 12x +1 -9
   = 5x² -18x -8

C = (3x-1)(x+4)-18x²+12x-2
    = (3x x x + 3x x 4 - 1 x x - 1 x 4 )-18x²+12x-2
    = (3x² + 12x - x - 4)-18x²+12x-2
    = 3x² + 11 x -4 -18x²+12x-2
    = 3x² - 18x² + 11x +12x - 4 - 2
    = 15x² + 23x - 6

Voila, j’espère t'avoir aider :D